Housing and mothering: their effects upon the developmental levels of 3-year-old children. Issue 1 (January 1979) - Pollak, M
Abstract : The development of 200 3-year-old children was measured, using Gesell parameters of development. The levels of development were matched against the adequacy, or inadequacy, of maternal care and housing, the scales for which were derived from a questionnaire completed by the children's mothers. Housing was not found to affect the children's developmental levels, while the adequacy of maternal care was highly significantly related to satisfactory child development.